Estradiol and Hyperhomocysteinemia Are Linked Predominantly Through Part Renal Function Indicators - Niu, Xiao Na; Wen, He; Sun, Nan; Yang, Yi; Du, Shi Hong; Xie, Rong; Zhang, Yan Nan; Li, Yan; Hong, Xiu Qin (Frontiers in Endocrinology, 2022)
Background Previous studies have shown that estrogen, kidney function, and homocysteine (Hcy) or hyperhomocysteinemia (HHcy) are related to each other. However, the underlying biological mechanisms still remain unclear. We aimed to explore the association between estradiol (E2) and HHcy in the female population, and to further evaluate the mediating role of renal function indicators. Methods This unmatched case–control study consisted of 1,044 female participants who were 60.60 ± 12.46 years old. Data on general demographic characteristics, such as age, smoking and drinking status, menopause and so on were collected in a personal interview, and laboratory examinations were performed by well-trained personnel. The mediating effect model was applied to analyze the direct and indirect effects of E2 on Hcy. Results The average levels of Hcy and E2 of the participants were 12.6 μmol/L and 14.95 pg/ml. There were statistical differences in renal indexes blood urea nitrogen (BUN), serum creatinine (Scr), uric acid (UA), glomerular filtration rate (GFR) and E2 between HHcy group and non-HHcy group. The logistic regression models showed that UA was risk factor for HHcy (P <0.001), GFR and E2 were protective factors for HHcy after adjusting for confounding factors (P <0.001). The indirect effects of E2 on Hcy through UA and GFR accounted for 14.63 and 18.29% of the total impacts of E2 on Hcy. Conclusions These data indicated that E2 was a protective factor of HHcy, and the effects of E2 on HHcy may be mediated by renal function indicators UA and GFR.